Ceramide synthase-6 confers resistance to chemotherapy by binding to CD95/Fas in T-cell acute lymphoblastic leukemia - Verlekar, Dattesh (Cell Death Dis, 2018)
Ceramide synthases (CERS) produce ceramides which are key intermediators in the biosynthesis of complex sphingolipids and play an important role in cell proliferation, differentiation, apoptosis and senescence. CERS6 is an isoform of ceramide synthases known to generate ceramides with C16 acyl chain (C(16)-Cer). CERS6 and C(16)-Cer levels were significantly higher in acute lymphoblastic leukemia (ALL) cells in comparison to peripheral blood mononuclear cells and T lymphocytes derived from healthy human volunteers. We investigated the role of CERS6 in chemo-resistance in T-ALL cell lines. Stable knockdown of CERS6 in CCRF-CEM and MOLT-4 cells resulted in increased sensitivity to ABT-737, a pan-BCL-2 inhibitor, while CCRF-CEM cells with exogenous CERS6 expression showed resistance to ABT-737 relative to the vector control. The cytotoxic activity of ABT-737 in CERS6 knockdown cells was significantly reduced by the addition of a caspase-8 inhibitor Z-IETD, suggesting that CERS6 alters the cytotoxicity via extrinsic pathway of apoptosis. By co-immunoprecipitation of CERS6 in CCRF-CEM cells, we identified CD95/Fas, a mediator of extrinsic apoptotic pathway, as a novel CERS6 binding partner. In Fas pull-down samples, FADD (Fas-associated protein with death domain) was detected at higher levels in cells with CERS6 knockdown compared with control cells when treated with ABT-737, and this was reversed by the overexpression of CERS6, demonstrating that CERS6 interferes with Fas–FADD DISC assembly. CERS6 may serve as a biomarker in determining the effectiveness of anticancer agents acting via the extrinsic pathway in T-ALL.